Conditioned Medium from Human Tonsil-Derived Mesenchymal Stem Cells Enhances Bone Marrow Engraftment via Endothelial Cell Restoration by Pleiotrophin - Yu-Hee Kim (Cells, 2020)
Cotransplantation of mesenchymal stem cells (MSCs) with hematopoietic stem cells (HSCs) has been widely reported to promote HSC engraftment and enhance marrow stromal regeneration. The present study aimed to define whether MSC conditioned medium could recapitulate the effects of MSC cotransplantation. Mouse bone marrow (BM) was partially ablated by the administration of a busulfan and cyclophosphamide (Bu−Cy)-conditioning regimen in BALB/c recipient mice. BM cells (BMCs) isolated from C57BL/6 mice were transplanted via tail vein with or without tonsil-derived MSC conditioned medium (T-MSC CM). Histological analysis of femurs showed increased BM cellularity when T-MSC CM or recombinant human pleiotrophin (rhPTN), a cytokine readily secreted from T-MSCs with a function in hematopoiesis, was injected with BMCs. Microstructural impairment in mesenteric and BM arteriole endothelial cells (ECs) were observed after treatment with Bu−Cy-conditioning regimen; however, T-MSC CM or rhPTN treatment restored the defects. These effects by T-MSC CM were disrupted in the presence of an anti-PTN antibody, indicating that PTN is a key mediator of EC restoration and enhanced BM engraftment. In conclusion, T-MSC CM administration enhances BM engraftment, in part by restoring vasculature via PTN production. These findings highlight the potential therapeutic relevance of T-MSC CM for increasing HSC transplantation efficacy.